STRATEGY OF BUMDES SINAR FAJAR IN DEVELOPING KALITEKUNG RIVER TOURISM AND KALITEKUNG CAFÉ IN TAMBAK CEMANDI VILLAGE, SIDOARJO - Nabila, Fira Shaafiyah; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study aims to analyze the development strategies implemented by BUMDes “Sinar Fajar” in managing Kalitekung River Tourism and Kalitekung Café as village-based economic units. This study focuses on organizational strategies, supporting resources, and promotional programs in strengthening local economic development and community empowerment. Method: This study uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews with key informants, including the Head of BUMDes, village government officials, café employees, and local residents, as well as observation and documentation analysis. Data validity was ensured through source triangulation, and analysis was conducted using interactive data analysis techniques. Results: Findings indicate that BUMDes “Sinar Fajar” has implemented integrated strategies, including a clear organizational vision and mission, community-based human resource utilization, collaborative partnerships, and digital and direct promotional strategies. These strategies have contributed to increased community participation, improved local employment opportunities, and greater visibility for village tourism. However, challenges remain, particularly related to operational constraints and environmental factors that affect tourism activities. Novelty: This study offers a new contribution by highlighting an integrated strategic model for BUMDes management that combines digital marketing, community empowerment, and collaborative governance in developing village tourism. These findings provide practical insights for strengthening sustainable village-owned enterprises without compromising local social values.